2000
DOI: 10.1046/j.1365-2508.2000.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical pelvic neuroablation for chronic pelvic pain: a systematic review

Abstract: Objective To determine, from the best available evidence, the effectiveness of surgical pelvic neuroablative techniques as treatment for primary and secondary dysmenorrhoea. Design Systematic review of randomized controlled trials (RCTs). Subjects Women with primary or secondary dysmenorrhoea. Interventions Surgical neuroablative techniques including uterine nerve ablation and presacral neurectomy. Main outcome measures Pain relief (both short‐ and long‐term) and adverse effects. Results Laparoscopic uterine n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…A power calculation has been undertaken to determine an appropriate sample size to demonstrate what was deemed to be a clinically important treatment effect of LUNA 12 . For women with chronic pelvic pain in the absence of endometriosis, to have 80% power at the 95% confidence level to detect benefit in 50% of women, assuming ‘benefit’ in 10% controls, at least 48 participants would be required for analysis following randomisation.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A power calculation has been undertaken to determine an appropriate sample size to demonstrate what was deemed to be a clinically important treatment effect of LUNA 12 . For women with chronic pelvic pain in the absence of endometriosis, to have 80% power at the 95% confidence level to detect benefit in 50% of women, assuming ‘benefit’ in 10% controls, at least 48 participants would be required for analysis following randomisation.…”
Section: Methodsmentioning
confidence: 99%
“…It was concluded that there was insufficient evidence to recommend the routine use of LUNA in the management of chronic pelvic pain, but suggested there may be a difference in response between women with endometriosis and those with chronic pelvic pain in the absence of endometriosis. There have been isolated case reports of uterine prolapse 13,14 and bladder dysfunction 15 following LUNA, although the complication rate attributable directly to LUNA appears to be extremely low 12 . Other adverse effects of neuroablation, such as haematoma formation, constipation and subsequent painless labour, appear to be more associated with presacral neurectomy (PSN) than LUNA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations